Interactions between tectonics, bedrock inheritance and geomorphic responses of rivers in a post-rifting upland (Ponta Grossa Arch region, Brazil) - dos Santos, Marcilene [UNESP]; Ladeira, Francisco Sergio Bernardes; Batezelli, Alessandro; Nunes, João Osvaldo Rodrigues [UNESP]; Salamuni, Eduardo; da Silva, Clauzionor Lima; Molina, Eder Cassola; Moraes, Isabel Cristina (FapUNIFESP (SciELO), 2022)
Tectonic rejuvenation has been widely described in ancient rifting areas of intraplate settings, despite extensive active tectonics being discontinued long ago. Various models have been invoked to justify such tectonic rejuvenation, suggesting that the long-term deformation in intraplate interiors may be more complex than once supposed. Inherited weakness zones, e.g., pre-existing faults are stress concentrators. However, not all weakness zones in plate interiors show tectonic rejuvenation and recognizing intraplate fault reactivation remains puzzling. Bedrock channels play an essential role in tectonically unstable landscapes and therefore they may unveil which pre-existing structures have been rejuvenated. Here we explore the Cinzas Catchment in order to investigate the interactions between tectonic rejuvenation, bedrock inheritance and geomorphic river signatures in an important Brazilian rifting feature, the Ponta Grossa Arch. We perform a geomorphic analysis combined with fieldwork, dating techniques and existing data to evaluate whether the geomorphic responses of the major rivers show perturbations related to the bedrock inheritance and post-rift rejuvenation. We also show that the interactions between river signatures and the bedrock fault zones are responses to post-rifting rejuvenation coupled with bedrock inheritance. This post-rifting rejuvenation is consistent with a mosaic of superimposed mechanisms which have been invoked by previous studies.
Keywords: bedrock inheritance; geomorphic analysis; post-rifting tectonics; Quaternary; tectonic rejuvenation